Coal gangue-based water stabilizing material and preparation method thereof

Through the combined use of modified gangue aggregate and modified polypropylene fiber, the problem of insufficient strength of coal gangue is solved, the strength and quality of water-stabilized materials are significantly improved, and the resource utilization of coal gangue is realized.

CN119430800APending Publication Date: 2025-02-14ANHUI WATER RESOURCES DEV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411608155.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Coal gangue has a large number of holes and cracks on its surface, which makes its hardness and strength weak, affecting its application in road engineering.

Method used

Through the combined use of modified gangue aggregate and modified polypropylene fiber, the modified gangue aggregate is modified by high-temperature calcination and silane coupling agent to increase its particle size distribution and surface charge, and the modified polypropylene fibers pass through The silane coupling agent is modified, dispersed evenly and interwoven in the matrix.

Benefits of technology

It significantly improves the strength and quality of water-stable material after forming, solves the problem of insufficient strength of coal gangue itself, and realizes the resource utilization of coal gangue.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of coal gangue recycling, in particular to a coal gangue-based water stabilizing material and a preparation method thereof.The coal gangue-based water stabilizing material is prepared from, by weight, 75-85 parts of modified coal gangue aggregate, 8-10 parts of modified polypropylene fiber, 5-10 parts of cement and 3-5 parts of water; the preparation method comprises the following steps: pouring the modified coal gangue aggregate and the modified polypropylene fiber into a stirrer for stirring; adding cement and water into the stirrer, and continuously stirring and mixing to obtain a water stabilizing material; and the water stabilizing material is injected into a mold and tamped, and demolding is carried out after curing. According to the invention, coal gangue is modified, so that the problem of weak strength of coal gangue due to more voids is solved, the strength of the formed water stabilizing material can be greatly improved by adding the modified coal gangue aggregate, and resource utilization of coal gangue is also realized; meanwhile, the modified polypropylene fibers are added, so that the modified polypropylene fibers are uniformly dispersed and interwoven in the matrix, and the quality of the water stabilizing material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal gangue recycling, in particular to a coal gangue-based water-stabilized material and a preparation method thereof. Background Art

[0002] Gangue is a kind of black-gray solid waste with low calorific value, low carbon content and harder than coal produced in the process of coal mining. The main components of gangue include silicon dioxide and aluminum oxide, and also contain small amounts of metal elements such as iron, magnesium and calcium. According to statistics, my country's annual output of gangue is about 300 million tons, of which 200 million tons can be used for power generation, but there is still a part of gangue that is difficult to process and cause harm to the environment. Gangue is a kind of waste that is difficult to mine, and its low carbon content makes it difficult to be processed and utilized. At present, the utilization rate of domestic gangue is low. By calcining the gangue at high temperature to remove impurities, crushing it into particles as aggregate to construct water-stabilized materials, the resource recycling of gangue can be effectively realized.

[0003] However, there are a large number of holes and cracks on the surface of gangue aggregate. Compared with ordinary crushed stone, the defects on the surface of gangue make its hardness and strength weaker, which seriously affects the application of gangue-based water-stabilized material in road engineering. Based on this, a gangue-based water-stabilized material and its preparation method are proposed. Summary of the invention

[0004] In order to address the deficiencies of the prior art, the present invention provides a gangue-based water-stabilized material and a preparation method thereof. By using modified gangue aggregate and modified polypropylene fiber in combination, the quality of the water-stabilized material after molding is greatly improved.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a gangue-based water-stabilized material, comprising the following raw materials in parts by weight: 75-85 parts of modified gangue aggregate, 8-10 parts of modified polypropylene fiber, 5-10 parts of cement, and 3-5 parts of water.

[0006] Preferably, the particle size of the modified coal gangue aggregate is between 1-10 mm; among which, the particle size between 1-3 mm accounts for 30-40%, the particle size between 3-5 mm accounts for 40-50%, and the particle size between 5-10 mm accounts for 10-30%.

[0007] Preferably, the cement is a slow-setting cement selected from grade 42.5.

[0008] Preferably, the modified polypropylene fiber is obtained by surface-modifying the polypropylene fiber with a silane coupling agent.

[0009] Preferably, the silane coupling agent is any one of vinyl triethoxysilane and methacryloxypropyl trimethoxysilane.

[0010] Preferably, the modified gangue aggregate is prepared as follows: S1, calcining the gangue at high temperature to obtain impurity-removed gangue; S2, crushing the impurity-removed gangue into gangue particles of various particle sizes, pouring the gangue particles into a hexadecyltrimethylammonium bromide solution, shaking them in a water bath, filtering, washing, and drying to obtain pretreated gangue particles; S3, stirring and mixing the pretreated gangue particles and ethyl orthosilicate, adding ammonia water to the obtained mixture, continuing to stir the reaction, and after the reaction is completed, filtering, washing, and calcining at high temperature to obtain modified gangue aggregate.

[0011] Preferably, in step S2, the concentration of the cetyltrimethylammonium bromide solution is 2-5 mmol / L; the solid-liquid ratio of the gangue particles to the cetyltrimethylammonium bromide solution is 1:50 g / ml.

[0012] Preferably, in step S2, the temperature of the water bath shaking treatment is 60-70° C. and the time is 2-3 h.

[0013] Preferably, in step S3, the volume ratio of tetraethyl orthosilicate to ammonia water is 1:3; the material-liquid ratio of pretreated coal gangue particles and tetraethyl orthosilicate-ammonia water is 1:3; and the stirring reaction time is 2-3 hours.

[0014] The present invention also provides a method for preparing a gangue-based water-stabilized material, comprising the following steps:

[0015] (1) Pour the modified coal gangue aggregate and the modified polypropylene fiber into a mixer and stir;

[0016] (2) Add cement and water into a mixer and continue stirring and mixing to obtain a water-stable material;

[0017] (3) Inject the water-stabilized material into the mold and tamp it down, then demould it after curing.

[0018] The present invention provides a gangue-based water-stabilized material and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0019] The present invention solves the problem that the strength of the coal gangue is relatively weak due to the large number of voids in the coal gangue by modifying the coal gangue. By adding the modified coal gangue aggregate, the strength of the water-stabilized material after molding can be greatly improved, and the resource utilization of the coal gangue can be realized. At the same time, the modified polypropylene fiber is added so that it is evenly dispersed and interwoven in the matrix, further improving the quality of the water-stabilized material.

[0020] The invention adopts hexadecyltrimethylammonium bromide to treat the coal gangue, so that the surface of the coal gangue carries positive charge groups, and the micro-nano silicon dioxide formed by hydrolysis-condensation of ethyl orthosilicate under the action of ammonia water has negative charge on the silanol bond carried by the micro-nano silicon dioxide, which can be adsorbed on the surface of the coal gangue through electrostatic attraction, and the coal gangue also provides a good carrier point for the generation of the micro-nano silicon dioxide, so that the micro-nano silicon dioxide is filled in the gaps and surface of the coal gangue, so as to improve the strength of the coal gangue. DETAILED DESCRIPTION

[0021] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0022] Example 1

[0023] The preparation of modified coal gangue aggregate is as follows:

[0024] S1, calcining the coal gangue at 700°C for 2h to obtain impurity-removed coal gangue;

[0025] S2, crushing the impurity-removed coal gangue into coal gangue particles of various particle sizes, pouring the coal gangue particles into a 5mmol / L hexadecyltrimethylammonium bromide solution at a material-liquid ratio of 1:50g / ml, shaking in a water bath at 60°C for 3h, filtering, washing and drying to obtain pretreated coal gangue particles;

[0026] S3, stirring and mixing the pretreated gangue particles and ethyl orthosilicate, adding ammonia water to the obtained mixture, continuing stirring and reacting for 2 hours, filtering, washing, and calcining at 500°C for 1.5 hours after the reaction is completed, to obtain modified gangue aggregate. Among them, the volume ratio of ethyl orthosilicate and ammonia water is 1:3; the material-liquid ratio of the pretreated gangue particles and ethyl orthosilicate-ammonia water (the total volume of ethyl orthosilicate and ammonia water) is 1:3.

[0027] Example 2

[0028] The preparation of modified coal gangue aggregate is as follows:

[0029] S1, calcining the coal gangue at 700°C for 2h to obtain impurity-removed coal gangue;

[0030] S2, crushing the impurity-removed coal gangue into coal gangue particles of various particle sizes, pouring the coal gangue particles into a 2mmol / L hexadecyltrimethylammonium bromide solution at a material-liquid ratio of 1:50g / ml, shaking in a water bath at 70°C for 2h, filtering, washing and drying to obtain pretreated coal gangue particles;

[0031] S3, stirring and mixing the pretreated gangue particles and ethyl orthosilicate, adding ammonia water to the obtained mixture, continuing stirring and reacting for 3 hours, filtering, washing, and calcining at 500°C for 1.5 hours after the reaction is completed, to obtain modified gangue aggregate. Among them, the volume ratio of ethyl orthosilicate and ammonia water is 1:3; the material-liquid ratio of the pretreated gangue particles and ethyl orthosilicate-ammonia water (the total volume of ethyl orthosilicate and ammonia water) is 1:3.

[0032] Example 3

[0033] The preparation of modified coal gangue aggregate is as follows:

[0034] S1, calcining the coal gangue at 700°C for 2h to obtain impurity-removed coal gangue;

[0035] S2, crushing the impurity-removed coal gangue into coal gangue particles of various particle sizes, pouring the coal gangue particles into 4mmol / L hexadecyltrimethylammonium bromide solution at a material-liquid ratio of 1:50g / ml, shaking in a water bath at 65°C for 2.5h, filtering, washing and drying to obtain pretreated coal gangue particles;

[0036] S3, the pretreated gangue particles and ethyl orthosilicate are stirred and mixed, ammonia water is added to the obtained mixture, and the stirring reaction is continued for 2.2 hours. After the reaction is completed, the mixture is filtered, washed, and calcined at 500°C for 1.5 hours to obtain modified gangue aggregate. Among them, the volume ratio of ethyl orthosilicate and ammonia water is 1:3; the material-liquid ratio of the pretreated gangue particles and ethyl orthosilicate-ammonia water (the total volume of ethyl orthosilicate and ammonia water) is 1:3.

[0037] Example 4

[0038] A gangue-based water-stabilized material comprises the following raw materials in parts by weight: 85 parts of the modified gangue aggregate in Example 1, 8 parts of modified polypropylene fiber, 10 parts of 42.5-grade slow-setting cement, and 3 parts of water.

[0039] The particle size of the modified coal gangue aggregate is between 1-10mm; among them, the particle size between 1-3mm accounts for 40%, the particle size between 3-5mm accounts for 40%, and the particle size between 5-10mm accounts for 20%. The modified polypropylene fiber is obtained by surface modification of polypropylene fiber with vinyl triethoxysilane.

[0040] The preparation method of the above-mentioned coal gangue-based water-stabilized material comprises the following steps:

[0041] (1) Pour the modified coal gangue aggregate and the modified polypropylene fiber into a mixer and stir;

[0042] (2) Add cement and water into a mixer and continue stirring and mixing to obtain a water-stable material;

[0043] (3) Inject the water-stabilized material into the mold and tamp it down, then demould it after curing.

[0044] Example 5

[0045] A gangue-based water-stabilized material comprises the following raw materials in parts by weight: 75 parts of the modified gangue aggregate in Example 2, 10 parts of modified polypropylene fiber, 5 parts of 42.5-grade slow-setting cement, and 5 parts of water.

[0046] The particle size of the modified coal gangue aggregate is between 1-10mm; among them, the particle size between 1-3mm accounts for 30%, between 3-5mm accounts for 40%, and between 5-10mm accounts for 30%. The modified polypropylene fiber is obtained by surface modification of polypropylene fiber with methacryloxypropyltrimethoxysilane.

[0047] The preparation method of the above-mentioned coal gangue-based water-stabilized material comprises the following steps:

[0048] (1) Pour the modified coal gangue aggregate and the modified polypropylene fiber into a mixer and stir;

[0049] (2) Add cement and water into a mixer and continue stirring and mixing to obtain a water-stable material;

[0050] (3) Inject the water-stabilized material into the mold and tamp it down, then demould it after curing.

[0051] Example 6

[0052] A gangue-based water-stabilized material comprises the following raw materials in parts by weight: 80 parts of the modified gangue aggregate in Example 3, 8 parts of modified polypropylene fiber, 7 parts of 42.5-grade slow-setting cement, and 4 parts of water.

[0053] The particle size of the modified coal gangue aggregate is between 1-10mm; among them, the particle size between 1-3mm accounts for 40%, the particle size between 3-5mm accounts for 50%, and the particle size between 5-10mm accounts for 10%. The modified polypropylene fiber is obtained by surface modification of polypropylene fiber with vinyl triethoxysilane.

[0054] The preparation method of the above-mentioned coal gangue-based water-stabilized material comprises the following steps:

[0055] (1) Pour the modified coal gangue aggregate and the modified polypropylene fiber into a mixer and stir;

[0056] (2) Add cement and water into a mixer and continue stirring and mixing to obtain a water-stable material;

[0057] (3) Inject the water-stabilized material into the mold and tamp it down, then demould it after curing.

[0058] Comparative Example 1

[0059] The method is basically the same as Example 6, except that the modified coal gangue aggregate is prepared as follows:

[0060] S1, calcining the coal gangue at 700°C for 2h to obtain impurity-removed coal gangue;

[0061] S2, crushing the impurity-removed coal gangue into coal gangue particles of various particle sizes;

[0062] S3, the gangue particles and ethyl orthosilicate are stirred and mixed, ammonia water is added to the obtained mixture, and the stirring reaction is continued for 2.2 hours. After the reaction is completed, the mixture is filtered, washed, and calcined at 500°C for 1.5 hours to obtain modified gangue aggregate. Among them, the volume ratio of ethyl orthosilicate and ammonia water is 1:3; the material-liquid ratio of gangue particles and ethyl orthosilicate-ammonia water (the total volume of ethyl orthosilicate and ammonia water) is 1:3.

[0063] Comparative Example 2

[0064] The method is basically the same as Example 6, except that the modified coal gangue aggregate is prepared as follows:

[0065] S1, calcining the coal gangue at 700°C for 2h to obtain impurity-removed coal gangue;

[0066] S2. The impurity-removed coal gangue is crushed into coal gangue particles of various particle sizes, and the coal gangue particles are poured into 4 mmol / L hexadecyltrimethylammonium bromide solution at a solid-liquid ratio of 1:50 g / ml. The mixture is shaken in a water bath at 65°C for 2.5 h. After filtering, washing and drying, pretreated coal gangue particles are obtained, which are recorded as modified coal gangue aggregate.

[0067] Comparative Example 3

[0068] A gangue-based water-stabilized material comprises the following raw materials in parts by weight: 80 parts of the modified gangue aggregate in Example 3, 7 parts of 42.5-grade slow-setting cement, and 4 parts of water.

[0069] The particle size of the modified coal gangue aggregate is between 1-10mm; among them, the particle size between 1-3mm accounts for 40%, the particle size between 3-5mm accounts for 50%, and the particle size between 5-10mm accounts for 10%.

[0070] The preparation method of the above-mentioned coal gangue-based water-stabilized material comprises the following steps:

[0071] (1) adding modified coal gangue aggregate, cement and water into a mixer, stirring and mixing to obtain a water-stable material;

[0072] (2) Inject the water-stabilized material into the mold and tamp it down, then demould it after curing.

[0073] Comparative Example 4

[0074] A gangue-based water-stabilized material comprises the following raw materials in parts by weight: 80 parts of the modified gangue aggregate in Example 3, 8 parts of polypropylene fibers, 7 parts of 42.5-grade slow-setting cement, and 4 parts of water.

[0075] The particle size of the modified coal gangue aggregate is between 1-10mm; among them, the particle size between 1-3mm accounts for 40%, the particle size between 3-5mm accounts for 50%, and the particle size between 5-10mm accounts for 10%.

[0076] The preparation method of the above-mentioned coal gangue-based water-stabilized material comprises the following steps:

[0077] (1) Pour the modified coal gangue aggregate and polypropylene fiber into a mixer and stir;

[0078] (2) Add cement and water into a mixer and continue stirring and mixing to obtain a water-stable material;

[0079] (3) Inject the water-stabilized material into the mold and tamp it down, then demould it after curing.

[0080] Quality Inspection

[0081] 1. The water-stabilized materials in Examples 4-6 and Comparative Examples 1-4 were used as samples, and their 7d unconfined compressive strength and splitting strength were tested according to the "Testing Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG 3441-2024). The specific test results are shown in the following table.

[0082] Table 1 Strength

[0083] category Unconfined compressive strength (MPa) Splitting strength(MPa) Example 4 8.29 0.74 Example 5 8.13 0.70 Example 6 8.45 0.77 Comparative Example 1 7.02 0.61 Comparative Example 2 5.84 0.55 Comparative Example 3 5.36 0.52 Comparative Example 4 6.81 0.60

[0084] From the above table, we can see that:

[0085] (1) The strength of the sample in Comparative Example 2 is far less than that in Example 6, indicating that the use of micro-nano silica to fill the gaps and surfaces of coal gangue can indeed improve the performance of coal gangue, thereby improving the quality of water-stabilized materials.

[0086] (2) The strength of the sample in Comparative Example 1 is slightly better than that in Comparative Example 2, but not as good as that in Example 6, indicating that by modifying the coal gangue particles, the coal gangue can be better combined with micro-nano silica, thereby enhancing the strength of the coal gangue itself.

[0087] (3) The strength of the sample in Comparative Example 3 is far inferior to that in Example 6, indicating that the addition of modified polypropylene fiber can directly improve the quality of the water-stabilized material.

[0088] (4) The sample strength of Example 4 is slightly better than that of Example 3, but not as good as that of Example 6, indicating that the surface modification of the polypropylene fiber can better combine with the inorganic phase matrix, which is conducive to the uniform dispersion and combination of the polypropylene fiber, thereby improving the quality of the water-stabilized material.

[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A coal gangue-based water-stabilized material, characterized in that: The invention comprises the following raw materials in parts by weight: 75-85 parts of modified coal gangue aggregate, 8-10 parts of modified polypropylene fiber, 5-10 parts of cement and 3-5 parts of water.

2. The gangue-based water-stabilized material according to claim 1, characterized in that: The particle size of the modified coal gangue aggregate is between 1-10 mm; among them, the particle size between 1-3 mm accounts for 30-40%, the particle size between 3-5 mm accounts for 40-50%, and the particle size between 5-10 mm accounts for 10-30%.

3. The gangue-based water-stabilized material according to claim 1, characterized in that: The cement is selected from 42.5 grade slow setting cement.

4. The gangue-based water-stabilized material according to claim 1, characterized in that: The modified polypropylene fiber is prepared by surface modification of polypropylene fiber by using a silane coupling agent.

5. The gangue-based water-stabilized material according to claim 4, characterized in that: The silane coupling agent is any one of vinyl triethoxysilane and methacryloxypropyl trimethoxysilane.

6. The gangue-based water-stabilized material according to claim 1, characterized in that: The preparation of the modified coal gangue aggregate is as follows: S1, calcining the coal gangue at high temperature to obtain impurity-removed coal gangue; S2, crushing the impurity-removed coal gangue into coal gangue particles of various particle sizes, pouring the coal gangue particles into a cetyltrimethylammonium bromide solution, performing a water bath shaking treatment, filtering, washing, and drying to obtain pretreated coal gangue particles; S3, stirring and mixing the pretreated coal gangue particles and ethyl orthosilicate, adding ammonia water to the obtained mixture, continuing to stir and react, and after the reaction is completed, filtering, washing, and high-temperature calcining to obtain modified coal gangue aggregate.

7. The gangue-based water-stabilized material according to claim 6, characterized in that: In step S2, the concentration of the hexadecyltrimethylammonium bromide solution is 2-5 mmol / L; the material-liquid ratio of the coal gangue particles to the hexadecyltrimethylammonium bromide solution is 1:50 g / ml.

8. The gangue-based water-stabilized material according to claim 6, characterized in that: In step S2, the temperature of the water bath shaking treatment is 60-70°C and the time is 2-3h.

9. The gangue-based water-stabilized material according to claim 6, characterized in that: In step S3, the volume ratio of tetraethyl orthosilicate to ammonia water is 1:3; the material-liquid ratio of pretreated coal gangue particles and tetraethyl orthosilicate-ammonia water is 1:3; and the stirring reaction time is 2-3 hours.

10. The method for preparing the gangue-based water-stabilized material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Pour the modified coal gangue aggregate and the modified polypropylene fiber into a mixer and stir; (2) Add cement and water into a mixer and continue stirring and mixing to obtain a water-stable material; (3) Inject the water-stabilized material into the mold and tamp it down, then demould it after curing.